Relationship between Self-Control and Pornography Addiction in Children who Experience Sexual Deviations in the City of Padang - Dini Widhya Anggraini; Netrawati Netrawati (Universitas Negeri Padang, 2021)
This research is based on the existence of nowadays children especially boys a lot of playing internet or online game, on an of internet site or online game there are advertisements that seem vulgar or content that refers to pornographic films or videos. Easy access to pornographic films or videos, allowing children to watch freely so that it becomes addictive to go back to watching porn movies or videos continuously. Addiction to pornography makes children unable to self-control and it is difficult to let go of these thoughts. Because you already feel attracted to these negative things, eventually there will be a sense of curiosity and want to try then deviate actions arise, namely taking it out by committing sexual violence to other people. It is interesting that the trend of the number of child victims of sexual violence and the number of child sexual violence perpetrators is relatively the same from year to year. So that many children become perpetrators of sexual violence.This study aims to: (1) Describe the level of self-control in children who experience sexual deviations, (2) Describe the level of pornography addiction in children who experience sexual deviations, and (3) Test the relationship between self-control and pornography addiction in children who experience sexual deviations. The research subjects were 43 students, using instruments with Likert scale models. The percentage analysis technique and to test the relationship of the data were analyzed using the Pearson Correlation Product Moment statistical formula with the help of the SPSS for Windows version 20.0 program. The results of the study revealed that: (1) the level of self-control in children who experience sexual deviations was classified as lower, (2) the level of pornography addiction in children who experience sexual deviations was classified as very high, and (3) there was a significant negative relationship between self-control and pornography addiction in children who experience sexual deviations with significance level 0,001, r count 0.3008, and r table -. 487.